Pemetaan Penelitian seputar Manajemen Zakat pada Lembaga Keuangan Syariah: Studi Bibliometrik VOSviewer dan Literature Review - Budianto, Eka Wahyu Hestya; Ibad, Nuzulul Nasoihul; Pratopo, Gentur; Dewi, Nindi Dwi Tetria (Jurnal Ekonomika dan Bisnis Islam, 2023)
This study aims to determine the development of research around Zakah Management in Islamic Financial Institutions. The research was conducted from 2013 to 2022, by searching national journals indexed by Sinta via the Garuda website, with the keyword “Zakah Management”. Based on the search results, there were 60 research articles, then inputted into the VOSviewer application and analyzed descriptively through a literature review study. The results showed that the number of publications had increased significantly every year. Furthermore, based on the results detected using the VOSviewer application, research related to Zakah Management is divided into 11 clusters and 133 items. Meanwhile, based on the results of a literature review study, there are 3 main themes related to Zakah Management in Islamic Financial Institutions.